2016
DOI: 10.14254/2071-789x.2016/9-1/18
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foreign Remittances on Poverty Alleviation: Global Evidence

Abstract: ABSTRACT. This study using an empirical analysis to examine the impact of foreign remittances along with some other variables (foreign aid, debt, human capital, inflation and income) on poverty alleviation in 39 countries including the lower middle, upper middle and high income countries. The study uses the data covering the period of 1990-2014 and the method of Panel fully modified OLS (FMOLS). The FMOLS estimates reveal that increase in income leads to decrease in poverty. Foreign remittances are found to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 52 publications
(43 reference statements)
7
60
0
3
Order By: Relevance
“…Among the studies that attempted to establish the relationship between poverty and remittance, the results largely reflect a positive relationship (Adam and Page 2005;Acosta 2008;Gupta et al 2009; Fuente 2010; Anyanwu and Erhijakpan 2010; Adam and Cuecuacha 2013; Akobeng 2016; Nahar and Arshad 2017; Vacaflores 2018; Tsaurai 2018). However, there are other studies that found the relationship to be dependent on the country of study, methodology and time under investigation (Azam et al 2016;Wangle and Devkota 2018). Adam and Page (2005) in a study on 71 developing countries investigated the impact of remittance on poverty.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Among the studies that attempted to establish the relationship between poverty and remittance, the results largely reflect a positive relationship (Adam and Page 2005;Acosta 2008;Gupta et al 2009; Fuente 2010; Anyanwu and Erhijakpan 2010; Adam and Cuecuacha 2013; Akobeng 2016; Nahar and Arshad 2017; Vacaflores 2018; Tsaurai 2018). However, there are other studies that found the relationship to be dependent on the country of study, methodology and time under investigation (Azam et al 2016;Wangle and Devkota 2018). Adam and Page (2005) in a study on 71 developing countries investigated the impact of remittance on poverty.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Tsaurai (2018), in a separate study on selected emerging market economies, found remittance to reduce poverty. Azam et al (2016) investigated the impact of remittance on poverty reduction in 39 lower-middle, upper-middle and high-income countries employing panel data. Remittance was found to have a positive impact on poverty reduction in upper-middle-income countries with a 1% increase in remittance, leading to a 0.2% reduction in poverty.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A brand augmentation procedure can be in two essential structures. To start with is the vertical brand expansion and the second is the flat brand augmentation (Völckner and Sattler, 2006;Abidin et al, 2016;Azam et al, 2016;Haseeb et al, 2014a;Haseeb et al, 2014b). The vertical brand expansion implies that another item is presented, and the parent mark has a similar item classification, however the distinction lies in its quality and value level (Keller and Aaker, 1992).…”
Section: Brand Extension Successmentioning
confidence: 99%
“…Now in this time there is no accord with researches regarding direct link among CSR and brand loyalty. This task of CSR influence customer conduct is very difficult direct link conceptualized past (Klein & Dawar, 2004;Abidin et al, 2016;Azam et al, 2016;Haseeb et al, 2014a;Haseeb et al, 2014b). While the dimensions of CSR are many of constructs, but it is still needed that to identify contrast how every constructs CSR issue proposed by consumers.…”
Section: Introductionmentioning
confidence: 99%